Properties and Phase Transitions of the Solid $β$-HMX: Different Force Fields (Journal of Atomic and Molecular Sciences, 2012)
The structure, cell volume and lattice constants of $β$-octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine ($β$-HMX) crystal are studied by using the classical molecular dynamics method. The variations of cell volume and lattice constants are presented and discussed under different pressures and temperatures. The main purpose of the present work is to understand effect of different force fields, the CVFF and PCFF force fields were used instead of usual COMPASS. It is found that the cell volume is less satisfactory, and there was an abrupt change at 370 K and 440 K for the lattice constants and cell volume with CVFF force field. However, for PCFF force field, an abrupt change occurred at 360 K and 430 K, respectively. It means that $β$-HMX may have phase transitions at these temperatures in accordance with experimental observation. It is suggested that selection of suitable force field play an important role in achieving desired accuracy of simulation results.